1993
DOI: 10.1038/jcbfm.1993.8
|View full text |Cite
|
Sign up to set email alerts
|

6-[18F]fluoro-l-DOPA Metabolism in Living Human Brain: A Comparison of Six Analytical Methods

Abstract: Summary:In 11 normal volunteers and six patients with Parkinson's disease, we compared six different analyses of dopaminergic fu nction with L-3, 4-dihydroxy-6-[18F]fluorophenylalanine (FDOPA) and positron emission tomography (PET). The caudate nucleus, putamen, and several reference regions were identified in PET images, using magnetic resonance imaging (MRI). The six analy ses included two direct determinations of DOPA decar boxylase activity (kr;, kj), the slope-intercept plot based on plasma concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…The occipital cortex (OCC) contains scant dopaminergic innervation; one can quantify striatal DA deficiency from the PUT:OCC ratio of 6-[ 18 F]fluorodopa-derived radioactivity [2,3]. Spatial resolution of conventional PET scanning is inadequate to visualize the substantia nigra (SN) in individuals.…”
Section: Abstract or Phrasesmentioning
confidence: 99%
“…The occipital cortex (OCC) contains scant dopaminergic innervation; one can quantify striatal DA deficiency from the PUT:OCC ratio of 6-[ 18 F]fluorodopa-derived radioactivity [2,3]. Spatial resolution of conventional PET scanning is inadequate to visualize the substantia nigra (SN) in individuals.…”
Section: Abstract or Phrasesmentioning
confidence: 99%
“…The striatal-to-occipital ratio (SOR) and the influx constant calculated with a graphical tissue reference approach (K i ref ) are commonly used as quantitative parameters in 18 F-FDOPA PET studies. They have been measured noninvasively in the dynamic mode with region-of-interest (ROI)-based approaches (9)(10)(11)(12). Both SOR and K i have been used to quantify regional dopamine metabolism and to reflect disease severity in PD (5,(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In addition, K occ has been proven by many investigators to provide a sensitive discrimination between brain uptake in healthy volunteers and patients with PD. Several studies have compared the disease-discriminating ability of K i and K occ (Vingerhoets et al, 1994(Vingerhoets et al, , 1996Morrish et al, 1998;Takikawa et al, 1994;Leenders et al, 1990;Hoshi et al, 1993), with K occ usually found to be the better discriminator. The conventional interpretation of K i and K occ is as markers of DA synthesis and storage.…”
mentioning
confidence: 99%